Factors Analysis Of Decision Consideration Of The Class I Immigration Office Banda Aceh On The Immigration Administrative Action In The Case Of Yousuf Karim - M. Al Mudawar (Journal of Law and Border Protection, 2022)
Law enforcement is a matter of applying the law from the basis of legal actions and legal relations in the life of society and the state. Law enforcement can be used both as a major and a narrow one, so that in general all legal subjects are involved in all legal actions. Any individual or legal entity that adopts a common legal basis. Basically, law enforcement against Yousuf Karim is regulated based on immigration criminal provisions in article 113 and article 126 letter c, but the reality on the ground is that Yousuf Karim is subject to Immigration Administrative Action sanctions in the form of an obligation to reside in the territory of Indonesia and detention in the Detention Room. Immigration Kanim Banda Aceh. Basically the role of law enforcement in the Yousuf Karim case is very important because there are office holders who have the authority and policies taken against a case for reasons of consideration and application of criminal acts as an effort to apply the last legal sanctions. based on explaining and knowing the reasons and considerations of the Immigration Office Class I TPI Banda Aceh providing Immigration Administrative Actions against Yousuf Karim Immigration law enforcement begins with important matters regarding immigration instruments, namely immigration matters which consist of a series of supervision of the crossing of people entering and leaving the territory of Indonesia. and a series of surveillance of foreigners in the territory of Indonesia, then the Immigration Officer has the right of authority in terms of giving Immigration Administrative sanctions against foreigners who are in the territory of Indonesia who carry out dangerous activities and are reasonably suspected of endangering security and public order or not respecting or disobeying the law enforcement